Concerts and music festivals: how to exploit digital development after the Covid-19 pandemic to create new sources of income - Neves, Letícia Queiroga das (2022)
Music has been a big part of what constitutes social life for thousands of years and, in this way, gives meaning to the socialization between people and their surroundings (DeNora, 2000; Roy and Dowd, 2010). Furthermore, live music events often take on characteristics that connect people in the reciprocity of emotions (Bensimon, 2012). When the outbreak of the Covid-19 pandemic began in December 2019 in China, it started to affect the live entertainment industry heavily, as in-person meetings were limited all around the world, causing the cancellation of hundreds of events. This situation, in addition to affecting the sector economically and jeopardizing the financial security of thousands of people, also affects the socialization and emotional issues of those who depend on music for their connective purposes (Bodner and Gilboa, 2009). A short-term solution found by the industry itself was to offer similar live experiences, but in digital format instead of face-to-face; these are known as live streams, and they present several different possibilities for performance models. It is important to emphasize that such a solution was only possible thanks to new enabling technologies developed. With vaccination against Covid-19 successfully spreading around the world, in-person gatherings are gradually taking place again, but the technological developments generated in this period will be present and will still be applied. Thus, from a more entrepreneurial and economic perspective, the research question of this study is then defined as: how to exploit digital development after the Covid-19 pandemic to create new sources of income? This research focuses on analyzing in depth several real and successful cases of live streams, understanding what characteristics made them successful, and which ones would potentially improve even more their financial and social results. From this analysis, the theoretical knowledge of human behavior, and the understanding of how the enabling technologies work, a framework is created that can be applied to create digital and live experiences even more remarkable for producers and their customers.